2021
DOI: 10.1136/jitc-2020-001749
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic depletion of CCR8+tumor-infiltrating regulatory T cells elicits antitumor immunity and synergizes with anti-PD-1 therapy

Abstract: BackgroundModulation and depletion strategies of regulatory T cells (Tregs) constitute valid approaches in antitumor immunotherapy but suffer from severe adverse effects due to their lack of selectivity for the tumor-infiltrating (ti-)Treg population, indicating the need for a ti-Treg specific biomarker.MethodsWe employed single-cell RNA-sequencing in a mouse model of non-small cell lung carcinoma (NSCLC) to obtain a comprehensive overview of the tumor-infiltrating T-cell compartment, with a focus on ti-Treg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 59 publications
5
86
0
Order By: Relevance
“…Whether the anti-CCR8 antibodies used functioned in part through induction of Treg cell depletion has yet to be formally tested. The hypothesis that therapeutic depletion of CCR8 + cells rather than blockade of CCR8 function leads to induction of anti-tumour immunity is indeed consistent with recently reported findings that administration of anti-CCR8 nanobodies with blocking function does not augment tumour immunity, but does so when provided the capability for ADCC [40].…”
Section: Discussionsupporting
confidence: 89%
“…Whether the anti-CCR8 antibodies used functioned in part through induction of Treg cell depletion has yet to be formally tested. The hypothesis that therapeutic depletion of CCR8 + cells rather than blockade of CCR8 function leads to induction of anti-tumour immunity is indeed consistent with recently reported findings that administration of anti-CCR8 nanobodies with blocking function does not augment tumour immunity, but does so when provided the capability for ADCC [40].…”
Section: Discussionsupporting
confidence: 89%
“… 75 Two recent preclinical studies demonstrated that anti-CCR8 antibodies with Fc-dependent ADCC activity selectively deplete tumor-infiltrating Tregs due to prominent CCR8 expression by the activated Tregs in the TME, leading to long-lasting antitumor immune responses and synergistic antitumor effects with PD-1 blockade. 130 131 …”
Section: Targeting Chemokine Receptors and Immune Checkpoint Molecules On Tregsmentioning
confidence: 99%
“…The elevated abundance of activated CD8 + T cells, was accompanied by both a decreased infiltration of FoxP3 + regulatory T cells (Tregs), as well as a reduced expression of CCR8 on the Tregs (Fig. 1t, u), indicative for reduced suppressive phenotype of these cells [33].…”
Section: Cd40 Agonist Therapy Repolarises B16f10 Tumours Resulting In Reduced Tumour Growthmentioning
confidence: 99%
“…6g). Both Tregs and neutrophils were shown to suppress CD8 + T cells in LLC tumours [33,42], which could be responsible for the lower initial abundance of CD8 + T cells in LLC tumours and their inability to expand upon αCD40 + αCSF1R treatment (Fig. 6h).…”
Section: Llc Tumours Do Not Respond To αCd40 Therapy When Combined With Tam/neutrophil Depleting Therapies Nor Therapies Boosting Cd8 + Tmentioning
confidence: 99%